Peran Kebijakan Pemerintah dalam Melindungi Eksistensi Petani Tembakau (Pendekatan Daya Saing Tembakau Vorstenlanden di DIY) - Budi Widayanto; Agus Santosa (Jurnal Dinamika Sosial Ekonomi, 2004)
The Topic of this paper in The Goverment Policy to Indonesian Farmers Existention Protect. This paper rise issue about how much competitiveness the Yogyakarta Distric Vodimlanden tobacco at the global market and how government will to farmers Existention Protect The Conclusion of this paper is Commodity of the tobacco has high compenteness in the global market that showed PCR and DRC index higher than one and the government policy need to farmers tobacco protectedKeywords: competitivenes, government policy, protection